Impact of pharmacists’ training on oral anticoagulant counseling: a randomized controlled trial (2019)
Objective: The study evaluated the impact of oral anticoagulant counseling training on the quality of counseling provided by pharmacists. Methods: A prospective RCT was conducted among 33 pharmacists from 23 pharmacies in Ibadan, Nigeria. Six mystery patients (MPs) who were either warfarin-naïve, experienced adverse drug reaction (ADR), or drug interaction (DI) to warfarin were used to assess pharmacists’ oral anticoagulant counseling quality at pre- and post-intervention. A 2-week online oral anticoagulant counseling training was given to the intervention group pharmacists. Quality of counseling was categorized as poor (0–20 %), fair (21–50 %), moderate (51–80 %), and optimal (81–100 %). Results: At pre-intervention, the quality of oral anticoagulant counseling provided to the MPs was poor. Post-intervention, the quality improved among pharmacists in the intervention group, from poor to fair for both warfarin-naïve MP and MP who experienced DI, and from fair to moderate for MP with ADR. Conclusion: Short-term online oral anticoagulant counseling training improved the quality of counseling provided by community pharmacists to mystery patients on warfarin. Practice implication: Online oral anticoagulant counseling training may be employed by pharmacists’ professional bodies intermittently to improve oral anticoagulant counseling